Eldecalcitol (ED-71), an analog of 1α, 25-dihydroxyvitamin D3 as a potential anti-cancer agent for oral squamous cell carcinomas. Issue 164 (November 2016) - Shintani, T.; Rosli, S.N.Z.; Takatsu, F.; Choon, Y.F.; Hayashido, Y.; Toratani, S.; Usui, E.; Okamoto, T.
Highlights: ED-71, an analog of 1, 25(OH)2 D3, was able to inhibit the growth of cancer cell lines in serum-free culture. The anti-tumor activity of ED-71 was much higher than that of 1, 25(OH)2 D3 in both UE and NA cells. ED-71 significantly induced expression of CYP24A1 in cancer cell lines and in human gingival fibroblasts. ED-71 induced CYP24A1 expression in oral cancer cell lines in a dose-dependent manner. ED-71 inhibited growth of A431-derived tumor in athymic mice. Abstract: We have previously reported that 1, 25(OH)2 D3 inhibits NF-κB activity and thus inhibits growth of OSCC cells in serum-free culture and down-regulates HBp17/FGFBP-1 expression, which is important for cancer cell growth and angiogenesis. Here, we have investigated the effects of ED-71, an analog of vitamin D3 (VD) on OSCC cell lines in serum-free culture. It is known that ED-71 has a stronger inhibitory effect on bone resorption compared to VD and other VD analogs. To the best of our knowledge, there was no report examining the potential of ED-71 as an anti-cancer agent for OSCC. We found that ED-71 is able to inhibit the growth of cancer cell lines at a concentration of hundred times lower than calcitriol. As Cyp24A1 was reportedly induced in cancer cells, we measured the expression of CYP24A1 in OSCC cell lines (NA and UE), A431 epidermoid carcinoma and normal fibroblast cell (gfi) in serum-free culture. As a result, CYP24A1 mRNA and the protein expression in the OSCC cells treated with ED-71 increased in a dose-dependent manner. However, in vivo experiment, in which the A431 cells were implanted in mice, tumor formation was reduced by the ED-71 treatment with no significant difference between Cyp24A1 expression in the tumors of ED-71-treated and control group, as analyzed by western blotting and immunohistochemistry. These results suggest that ED-71 is a potential anti-cancer agent for OSCC.